Apropiación y resignificación del pensamiento clásico en Seniloquium - Randazzo, Maria Belen (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2021)
This paper proposes an approach to Seniloquium, a work of fundamental importance in Spanish literature, since it is the first manuscript collection of proverbs, composed at the end of the fifteenth century. It is also a text of singular characteristics: it includes almost 500 proverbs in Romance language, of common use at the end of the late Castilian Middle Ages, which the author orders alphabetically and explains through Latin comments, making use of very diverse written and oral sources. In this opportunity, we intend to analyze the different ways of inserting the thought of the classical Antiquity in Seniloquium’s comments.